2013
DOI: 10.1186/1471-2369-14-263
|View full text |Cite
|
Sign up to set email alerts
|

Predicting risk of mortality in dialysis patients: a retrospective cohort study evaluating the prognostic value of a simple chest X-ray

Abstract: BackgroundClinical outcomes of dialysis patients are variable, and improved knowledge of prognosis would inform decisions regarding patient management. We assessed the value of simple, chest X-ray derived measures of cardiac size (cardiothoracic ratio (CTR)) and vascular calcification (Aortic Arch Calcification (AAC)), in predicting death and improving multivariable prognostic models in a prevalent cohort of hemodialysis patients.MethodsEight hundred and twenty-four dialysis patients with one or more postero-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 24 publications
0
26
2
Order By: Relevance
“…On the other hand, about 75% of our patients had a CTR >50%, which was higher than the 42% [17], 59% [31] and 67% [30] previously described, although the prevalence of cardiovascular disease was about 20% in the present and previous studies. We used a database that was created from information obtained when patients with ESKD started renal replacement therapy.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…On the other hand, about 75% of our patients had a CTR >50%, which was higher than the 42% [17], 59% [31] and 67% [30] previously described, although the prevalence of cardiovascular disease was about 20% in the present and previous studies. We used a database that was created from information obtained when patients with ESKD started renal replacement therapy.…”
Section: Discussioncontrasting
confidence: 51%
“…The mean and median CTRs in the present study were about 55%, which is similar to that found in a previous study of patients on HD [30]. On the other hand, about 75% of our patients had a CTR >50%, which was higher than the 42% [17], 59% [31] and 67% [30] previously described, although the prevalence of cardiovascular disease was about 20% in the present and previous studies.…”
Section: Discussioncontrasting
confidence: 41%
“…The grade of AAC using a previously validated scoring system was assessed: grade 0 (no visible calcification), grade 1 (small spots of calcification or single thin calcification of the aortic handle), grade 2 (one or more areas of thick calcification) and grade 3 (circular calcification of the aortic knob). All measurements of AAC and CTR were assessed independently by three adjudicators, with disagreements resolved by a consensus measurement [31,32]. …”
Section: Methodsmentioning
confidence: 99%
“…It usually indicates the LV size and may provide reasonable estimates of vascular calcification [32]. …”
Section: Introductionmentioning
confidence: 99%
“…The principal design of the J-ACCESS 3 study was previously described (5,6 showing aortic calcification in CXR. The aortic calcification was visually assessed using CXR (11). Eighty-two subjects were excluded as a CXR and echocardiography examination was not performed.…”
Section: Study Populationmentioning
confidence: 99%